Modelo construtivista de avaliação de desempenho do processo de planejamento de compras no poder judiciário do estado de Santa Catarina - Silva, Guilherme Mattos da (2017)
One of the fields in evidence in Brazilian public administration, even for the mechanisms of the State of collection and provision services to society, is the field of public procurement, in which a representative part of the resources are used in the purchase of materials or in the contracting of private services, to serve the public purpose. The practices and procedures of purchases management in the Brazilian public administration are specifics, characterized by the excesses of uniform procedures and of formalism, making them specific and away from the reality of purchases of the supply chain of the private initiative or even of public purchases from other countries. The present study was motivated by the desire to understand and contribute to the improvement of the context of public procurement in Brazil and, given the different realities of procurement management, that of the Brazilian public administration and the wide range of recent scientific production, this research sought in the field of Performance Evaluation is a means of producing reflections and advances in the first. The research proposed the structuring of a decision support model, seeking to highlight the scientific contribution of the Performance Evaluation applied to the public procurement planning process in Brazil. For this, used two instruments: Proknow-C (Knowledge Development Process-Constructivist), applied in the selection of the bibliographic portfolio and in the systemic analysis of the literature, which allowed to identify knowledge gaps and opportunities of scientific contribution; and the MCDA-C (Multicriteria Decision Aid-Constructivist), applied to the construction of a performance evaluation model, through a case study in the Court of Justice in the State of Santa Catarina. The results show the contribution of the principles of Performance Evaluation in the decision-making process for procurement planning in the Court of Justice. The opportunities for scientific contribution were identified through the formation of a bibliographic portfolio and the bibliometric and systemic analyzes of the portfolio, which evidenced the opportunities. As a contribution, a model for evaluating the performance of the Court of Justice procurement planning process was presented, consisting of 26 indicators, for which the current conditions and established performance targets were identified. Final considerations were made with the contribution of the performance evaluation model and, especially, the knowledge generated from the construction process.